De hibridismos y alteridades en el ámbito teatral del siglo xvii: una «famosa jácara» - Elena Di Pinto (Mélanges de la Casa de Velázquez)
The hybrid forms used on the stage were very fruitful, in financial and literary terms, for theatrical practice in the 17th century. The author here offers a brief review of that hybridism, and the edition and analysis of a ground-breaking piece by way of example. The opuscule in question partakes of the oral nature of the crónica negra (local events and gossip), taking in the subject and the language of «normal» jácaras—it is a particular type of jácaras de sucesos (events)—and adds a new twist to this «mixture» to dramatise the chronicle. This is yet another example of the subtle shifting between reality and fiction that was so common in the Golden Age, and which in this case mingles genres, styles and purposes to achieve a mixed work—with a journalistic title, a gloomy and edifying tone, and a moral at the end.